Positive pole piece, battery and electric equipment

By regulating the lattice shrinkage and thickness ratio of the positive electrode active material layer and adding a hydrophobic conductive layer, the problem of poor charging and discharging capacity matching in the layering setting of the positive electrode active material layer is solved, and the cycle stability and energy density are improved.

CN119314999AActive Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310847346.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-11
Publication Date
2025-01-14
Estimated Expiration
2043-07-11

AI Technical Summary

Technical Problem

In the prior art, the layered arrangement of the positive electrode active material layer leads to poor matching of charge and discharge capacity, affecting cycle stability.

Method used

By regulating the ratio between the lattice shrinkage rate of the outer positive electrode active material and the thickness ratio of the inner active material layer, we ensure that the adjacent active material layers have a relatively matching charge and discharge capacity, and adopt a multi-layer active material layer structure, including the first A positive electrode active material layer and a second positive electrode active material layer are added thereto, and a hydrophobic conductive layer is added to improve the conductivity and stability.

Benefits of technology

The cycle stability and energy density of the positive electrode sheet are improved, cracks and crushing of the active material layer are reduced, charge and discharge capabilities are enhanced, and the stability and energy density of the material are taken into account.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314999A_ABST
    Figure CN119314999A_ABST
Patent Text Reader

Abstract

The invention discloses a positive pole piece, a battery and electric equipment, the positive pole piece comprises a positive active material layer, the positive active material layer comprises a first positive active material layer and a second positive active material layer, the second positive active material layer is located at the outer side of the first positive active material layer, and the second positive active material layer comprises a second positive active material; wherein the proportion of the thickness of the first positive electrode active material layer in the total thickness of the positive electrode active material layer is H, and the unit is%; the lattice volume shrinkage rate of the second positive electrode active material is V, and the unit is%; in the positive pole piece, the ratio of the lattice shrinkage rate of the positive active material on the outer side to the thickness ratio of the active material layer on the inner side is regulated and controlled to meet a certain range, so that the adjacent active material layers have relatively matched charging and discharging capacities, and the cycle stability is favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery, and an electrical device. Background Art

[0002] As the requirements for energy density and stable performance increase, some technical solutions propose to use positive electrode active materials with different characteristics in layers. However, the charge and discharge capabilities of the layered active material layers are usually poorly matched, which affects the cycle stability. Summary of the invention

[0003] In view of the above problems, the present application provides a positive electrode plate, a battery and an electrical device, wherein the charge and discharge capabilities of the layered active material layers are well matched, thereby improving the cycle stability.

[0004] The embodiment of the present application is implemented as follows:

[0005] In a first aspect, an embodiment of the present application provides a positive electrode sheet, the positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the second positive electrode active material layer is located outside the first positive electrode active material layer, and the second positive electrode active material layer includes a second positive electrode active material; wherein the thickness of the first positive electrode active material layer accounts for H in the total thickness of the positive electrode active material layer, in units of %; the lattice volume shrinkage rate of the second positive electrode active material is V, in units of %; the relationship between V and H satisfies:

[0006] In the technical solution of the embodiment of the present application, the ratio between the lattice shrinkage rate of the outer positive electrode active material and the thickness ratio of the inner active material layer is regulated to meet a certain range, so that the adjacent active material layers have a more matched charge and discharge capacity, which is beneficial to improving the cycle stability.

[0007] In some embodiments, V and H satisfy the following relationship:

[0008] In these embodiments, the ratio of the V value to the H value satisfies a further range, so that adjacent active material layers have more matched charge and discharge capabilities, which is beneficial to better improve the cycle stability.

[0009] In some embodiments, the value of V satisfies: 2%≤V≤4%; optionally, the value of V satisfies: 2%≤V≤3%.

[0010] In these embodiments, the second positive electrode active material has a smaller lattice shrinkage rate, which is beneficial to improve the cracking and breaking of the second positive electrode active material; at the same time, it is beneficial to control the ratio of the V value to the H value within a suitable range, which can improve the cycle stability. In addition, when the V value condition is met, there are more ternary positive electrode materials (such as nickel-cobalt-manganese ternary materials) to choose from, which is beneficial to improve the energy density.

[0011] In some embodiments, the value of H satisfies: 14%≤H≤61%; optionally, the value of H satisfies: 14%≤H≤39%.

[0012] In these embodiments, the thickness ratio of the inner active material layer meets a certain range. When the ratio requirements of the V value and the H value are met, the V value can meet a suitable range, which is conducive to better improving the cycle stability. At the same time, it is conducive to better matching the first positive electrode active material layer and the second positive electrode active material layer and exerting their respective functions; when the first positive electrode active material in the first positive electrode active material layer includes a highly stable lithium-containing phosphate, the thickness ratio of the first positive electrode active material layer is above a certain standard, and the first positive electrode active material layer also has a certain charge and discharge capacity, which is conducive to improving the cycle stability.

[0013] In some embodiments, the first positive electrode active material layer includes a first positive electrode active material, and the specific surface area BET of the first positive electrode active material satisfies: 7m 2 / g≤BET≤24m 2 / g; Optionally, BET satisfies: 9m 2 / g≤BET≤22m 2 / g.

[0014] In these embodiments, the specific surface area BET of the first positive electrode active material is above a certain standard, so that it has good electrochemical activity; the specific surface area BET of the first positive electrode active material is below a certain standard, which can improve the deterioration of the cycle stability caused by water absorption of the material.

[0015] In some embodiments, the first positive electrode active material layer includes a first positive electrode active material, the first positive electrode active material includes a doped or undoped lithium-containing phosphate; and / or the second positive electrode active material includes a ternary positive electrode material.

[0016] In these embodiments, the lithium-containing phosphate has good stability, and the ternary positive electrode material has a high energy density, which is beneficial to achieve both good cycle stability and energy density.

[0017] In some embodiments, the lithium-containing phosphate includes Li 1+x Mn 1-y A y P 1-z E zO4, -0.100 ≤ x ≤ 0.100, 0.001 ≤ y ≤ 0.500, 0.001 ≤ z ≤ 0.100, element A includes one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb or Ge; element E includes one or more of B, Si, N, S, F, Cl or Br; and / or the ternary cathode material includes Li a Ni b Co c M1 d M2 e O f R g , 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, element M1 includes Mn and / or Al, element M2 includes one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W or Nb, and element R includes one or more of N, F, S or Cl.

[0018] In these examples, the lithium-containing phosphate has good electrochemical performance, such as good stability.

[0019] In these examples, the ternary cathode material has good electrochemical performance, such as high energy density, appropriate lattice shrinkage rate, etc.

[0020] In some examples, the lithium-containing phosphate includes Fe element, and the ternary cathode material includes Mn element; in the positive electrode active material layer, the mass ratio of Fe element to Mn element is 0.03 - 0.25; optionally, the mass ratio of Fe element to Mn element is 0.05 - 0.20.

[0021] In these examples, the mass ratio of Fe element to Mn element satisfies a certain range, which is beneficial to regulating the H value within an appropriate range, thereby better improving the cycle stability.

[0022] In some examples, the positive electrode active material further includes at least one coating layer covering at least part of the surface of the first positive electrode active material and / or the second positive electrode active material, wherein the coating layer includes one or more of oxides, nitrates, phosphates or carbonates containing specified elements, and the specified elements include one or more of Al, Ba, Zn, Ti, Co, W, Y, Si, Sn, B or P; and / or the coating layer includes one or more of pyrophosphates, phosphates or carbon.

[0023] In these examples, the coating layer can modify the positive electrode active material.

[0024] In some embodiments, the positive electrode plate further includes a hydrophobic conductive layer, the hydrophobic conductive layer is located between the first positive electrode active material layer and the second positive electrode active material layer, and the hydrophobic conductive layer includes a hydrophobic conductive material.

[0025] In these embodiments, the hydrophobic conductive layer has both hydrophobic and conductive functions. The conductive function enables the first positive electrode active material layer and the second positive electrode active material layer to maintain good conductivity, and the hydrophobic function is beneficial to improving cycle stability.

[0026] In some embodiments, the hydrophobic conductive material includes a hydrophobic conductive polymer and a hydrophobic conductive carbon.

[0027] In these embodiments, the combination of the hydrophobic conductive polymer and the hydrophobic conductive carbon can provide better conductivity and hydrophobicity.

[0028] In some embodiments, the hydrophobic conductive polymer includes one or more of polypyrrole, polyaniline, polythiophene, or polyacetylene; and / or the hydrophobic conductive carbon includes one or more of hydrophobic carbon nanotubes or hydrophobic carbon nanofibers.

[0029] In these embodiments, the hydrophobic conductive polymer and the hydrophobic conductive carbon are appropriately selected and can better meet the performance requirements of the hydrophobic conductive material.

[0030] In some embodiments, in the hydrophobic conductive material, the mass proportion of the hydrophobic conductive carbon is 2% to 10%.

[0031] In these embodiments, the hydrophobic conductive carbon has a suitable mass proportion in the hydrophobic conductive material, so that the performance requirements for the hydrophobic conductive material can be better met.

[0032] In a second aspect, an embodiment of the present application provides a battery, comprising the positive electrode plate of the above embodiment.

[0033] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery of the above embodiment.

[0034] The above description is only an overview of the technical solution of the embodiment of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0036] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;

[0037] Figure 2 An exploded view of a battery provided for some embodiments of the present application;

[0038] Figure 3 An exploded view of a battery cell provided for some embodiments of the present application;

[0039] Figure 4 A schematic diagram of the structure of a first positive electrode sheet provided in some embodiments of the present application;

[0040] Figure 5 A schematic diagram of the structure of the second positive electrode plate provided in some embodiments of the present application.

[0041] icon:

[0042] 1000-Vehicles;

[0043] 100-battery; 200-controller; 300-motor;

[0044] 10-box; 11-first part; 12-second part; 13-accommodating space;

[0045] 20-battery cell; 21-housing; 22-electrode assembly; 23-electrode terminal; 24-pressure relief structure;

[0046] 211-housing; 212-cover; 213-sealed space;

[0047] 221-positive electrode sheet; 2211-positive electrode current collector; 2212-positive electrode active material layer; 2212a-first positive electrode active material layer; 2212b-second positive electrode active material layer; 2213-hydrophobic conductive layer;

[0048] A-thickness direction of the positive electrode sheet. DETAILED DESCRIPTION

[0049] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0050] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0052] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0053] In the description of the embodiments of the present application, the technical term "and / or", such as "Feature 1 and / or Feature 2", means that it can be "Feature 1" alone, it can be "Feature 2" alone, or it can be "Feature 1" plus "Feature 2". In addition, the character " / " in this article generally indicates that the objects before and after are in an "or" relationship.

[0054] In the description of the embodiments of the present application, unless otherwise specified, the meaning of “multiple” in “one or more” is two or more than two.

[0055] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0056] In the embodiments of the present application, the same reference numerals represent the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments. It should be understood that the heights, lengths, widths, and other dimensions of the various components in the embodiments of the present application shown in the drawings, as well as the overall heights, lengths, widths, and other dimensions of the integrated device are only exemplary descriptions and should not constitute any limitation to the present application.

[0057] From the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0058] In the production process of lithium-ion secondary battery electrode plates, single-layer coating is usually used to coat the required active material on the current collector. With the increase in requirements for energy density and stability performance, some technical solutions propose to use positive electrode active materials with different characteristics in layers, such as using positive electrode active materials with high energy density characteristics (such as ternary system materials) and positive electrode active materials with high stability characteristics (such as lithium-containing phosphates) in layers to take into account both energy density and stability.

[0059] During the cycle, the active materials on the outside of the positive electrode active material layer are closer to the negative electrode, so the lithium deintercalation reaction occurs more easily. The actual degree of lithium deintercalation caused by charging and discharging is greater than the apparent degree of lithium deintercalation (for example, the apparent charge and discharge voltage range is 2.5V to 4.4V, and the actual charge and discharge voltage range is 2.45V to 4.45V). A wider charge and discharge range will bring a greater volume change to the active material, and a greater volume change will easily cause cracks and breakage in the active material, thus affecting the cycle stability.

[0060] The lattice shrinkage rate can regulate the volume change. The material with a smaller lattice shrinkage rate has a smaller volume change, which can improve the cracking and breakage of the active material on the outside. However, the material with a smaller lattice shrinkage rate has poor rate performance and is not easily compatible with the adjacent active material layer, which also affects the cycle stability.

[0061] Although the mechanism of the technical solution of coating multiple layers of active material is not very clear, the inventor of the present application found that: when the material type of the active material is certain, when the rate performance of the active material is reduced, the active material layer needs to have a larger proportion in the multi-layer active material layer to exert a charge and discharge capacity that is more matched with the adjacent active material layer, so that the active material layers have better matching, which is conducive to improving the cycle stability. In other words, when the types of active materials on the inside and outside are certain, when the lattice shrinkage rate of the active material on the outside increases, its rate performance improves, the thickness of the active material layer on the outside needs to be reduced, and the corresponding thickness of the active material layer on the inside needs to be increased; conversely, the same logic applies.

[0062] Based on this, the present application provides a positive electrode plate, which regulates the ratio between the lattice shrinkage rate of the positive electrode active material on the outside and the thickness ratio of the active material layer on the inside to meet a certain range. That is to say, when the lattice shrinkage rate of the positive electrode active material on the outside increases, the corresponding active material layer on the inside has a relatively larger thickness ratio, and when the lattice shrinkage rate of the positive electrode active material on the outside decreases, the corresponding active material layer on the inside has a relatively smaller thickness ratio, so that adjacent active material layers have more matched charging and discharging capabilities, which is beneficial to improving cycle stability.

[0063] The battery cell using the positive electrode sheet disclosed in the embodiment of the present application can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft. The embodiment of the present application provides an electrical device using a battery as a power source, and the electrical device can be, but not limited to, a mobile phone, a tablet, a laptop computer, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, and the like. Among them, the electric toy can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and the spacecraft can include airplanes, rockets, space shuttles, and spacecrafts, and the like.

[0064] For the convenience of explanation, the following embodiments are described by taking a vehicle as an example of an electrical device in an embodiment of the present application.

[0065] See also Figure 1 , Figure 1A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0066] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0067] In the present application, the battery 100 refers to a single physical module including one or more battery cells 20 to provide a certain voltage and capacity, which may be in the form of a battery pack, a battery module, etc. The battery 100 may include a box 10 for encapsulating one or more battery cells 20, and the box 10 may prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.

[0068] See also Figure 2 , Figure 2 An exploded view of a battery 100 provided for some embodiments of the present application. The battery 100 includes a box 10 and a plurality of battery cells 20, and the plurality of battery cells 20 are accommodated in the box 10. Among them, the box 10 is used to accommodate the battery cells 20, and the box 10 can be a variety of structures. In some embodiments, the box 10 can include a first part 11 and a second part 12, the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a receiving space 13 for accommodating the battery cells 20. The second part 12 can be a hollow structure with one end open, the first part 11 is a plate-like structure, and the first part 11 covers the open side of the second part 12 to form a box 10 with a receiving space 13; the first part 11 and the second part 12 can also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12 to form a box 10 with a receiving space 13. Of course, the first part 11 and the second part 12 can be a variety of shapes, such as a cylinder, a cuboid, etc.

[0069] In the battery 100, multiple battery cells 20 can be connected in series, in parallel, or in a hybrid connection. A hybrid connection means that multiple battery cells 20 are both connected in series and in parallel. Multiple battery cells 20 can be directly connected in series, in parallel, or in a hybrid connection, and then the whole formed by multiple battery cells 20 is accommodated in the box 10. Alternatively, multiple battery cells 20 can be connected in series, in parallel, or in a hybrid connection to form a module, and multiple modules can be connected in series, in parallel, or in a hybrid connection to form a whole, and then accommodated in the box 10. The battery 100 can also include other structures. For example, multiple battery cells 20 can be electrically connected through a busbar component to achieve parallel, series, or hybrid connection of multiple battery cells 20.

[0070] The battery cell 20 refers to the smallest unit constituting the battery pack and can be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery or a magnesium-ion battery, but is not limited thereto.

[0071] See also Figure 3 The battery cell 20 may include a housing 21 , an electrode assembly 22 and an electrolyte, and both the electrode assembly 22 and the electrolyte are contained in the housing 21 .

[0072] The housing 21 may include a shell 211 and a cover 212. The shell 211 is a component used to cooperate with the cover 212 to form an internal sealed space 213 of the battery cell 20, wherein the formed sealed space 213 can be used to accommodate the electrode assembly 22, electrolyte and other components. The cover 212 refers to a component that covers the opening of the shell 211 to isolate the internal environment of the battery cell 20 from the external environment. The shape of the cover 212 can be adapted to the shape of the shell 211 to cooperate with the shell 211, and the cover 212 may also be provided with functional components such as electrode terminals 23 and pressure relief structures 24. A sealing ring may be configured between the opening of the shell 211 and the cover 212 to achieve sealing between the shell 211 and the cover 212.

[0073] The shell 211 and the cover 212 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shapes of the shell 211 and the cover 212 can be determined according to the specific shape and size of the electrode assembly 22. The shell 211 and the cover 212 can be made of various materials, such as but not limited to metals such as copper, iron, aluminum, stainless steel, and aluminum alloy. The sealing ring can be made of various materials, such as but not limited to PP (polypropylene), PC (polycarbonate), PET (polyethylene terephthalate) and other materials that are resistant to electrolyte corrosion, high toughness and fatigue resistance. A coating can be formed on the outer surface of the shell 211, and the material of the coating can be various, such as but not limited to corrosion-resistant materials such as Ni and Cr.

[0074] The battery cell 20 may also be in a soft pack form, such as a bag-type soft pack. The material of the soft pack may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0075] The electrode assembly 22 includes a negative electrode sheet, a separator and a positive electrode sheet 221 (see Figure 4 and Figure 5 ). The battery cell 20 mainly relies on the movement of metal ions between the positive electrode sheet 221 and the negative electrode sheet to work. During the charge and discharge process, the active ions are embedded and removed back and forth between the positive electrode sheet 221 and the negative electrode sheet; the isolation film is arranged between the positive electrode sheet 221 and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. The electrode assembly 22 can be a winding structure or a stacked structure, and the embodiments of the present application are not limited to this.

[0076] The negative electrode sheet includes a negative electrode collector, a negative electrode tab and a negative electrode active material layer. The negative electrode active material layer is arranged on at least one side of the negative electrode collector. A primer layer may also be arranged between the negative electrode active material layer and the negative electrode collector. The negative electrode tab protrudes from the negative electrode collector. The negative electrode tab is located at one end or two opposite ends of the negative electrode collector, for example.

[0077] Among them, the negative electrode current collector can be a metal foil or a composite current collector. For example, the material of the negative electrode current collector and the negative electrode tab can be copper. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0078] The negative electrode active material in the negative electrode active material layer may be a negative electrode active material such as carbon and silicon. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active material materials may also be used.

[0079] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0080] In some embodiments, the negative electrode active material layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0081] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0082] The isolation membrane is located between the positive electrode plate 221 and the negative electrode plate, and plays an isolation role. The embodiment of the present application has no particular restriction on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected.

[0083] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0084] See also Figure 4 and Figure 5 The positive electrode sheet 221 includes a positive electrode current collector 2211 and a positive electrode active material layer 2212 . The positive electrode active material layer 2212 is disposed on at least one side of the positive electrode current collector 2211 . A primer layer or the like may be disposed between the positive electrode active material layer 2212 and the positive electrode current collector 2211 .

[0085] Among them, the positive electrode current collector 2211 can be a metal foil or a composite current collector, for example, the material of the positive electrode current collector 2211 can be aluminum. The composite current collector may include a polymer material base layer and a metal layer formed on at least one side of the polymer material base layer, and the composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0086] The design requirements of the positive electrode active material layer 2212 can be designed according to the technical solutions proposed in the embodiments of the present application, unless otherwise specified.

[0087] In some embodiments, the positive electrode active material layer 2212 may further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0088] In some embodiments, the positive active material layer 2213 may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0089] Next, the positive electrode plate 221 proposed in the embodiment of the present application is described in detail.

[0090] See also Figure 4 In a first aspect, an embodiment of the present application provides a positive electrode sheet 221, the positive electrode sheet 221 includes a positive electrode active material layer 2212, the positive electrode active material layer 2212 includes a first positive electrode active material layer 2212a and a second positive electrode active material layer 2212b, the second positive electrode active material layer 2212b is located outside the first positive electrode active material layer 2212a, and the second positive electrode active material layer 2212b includes a second positive electrode active material; wherein the thickness of the first positive electrode active material accounts for H in the total thickness of the positive electrode active material layer 2212, in %; the lattice volume shrinkage rate of the second positive electrode active material layer 2212b is V, in %; the relationship between V and H satisfies:

[0091] The second positive electrode active material layer 2212b is located outside the first positive electrode active material layer 2212a, which means that the second positive electrode active material layer 2212b is located on the side of the first positive electrode active material layer 2212a away from the positive electrode current collector 2211. In the embodiment of the present application, the description of the active material layer being located inside and outside refers to its relative position in the electrode sheet; that is, in the first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b, the inside active material layer refers to the first positive electrode active material layer 2212a, and the outside active material layer refers to the first positive electrode active material layer 2212a.

[0092] The first positive electrode active material layer 2212 a includes a first positive electrode active material. Exemplarily, the first positive electrode active material and the second positive electrode active material are of different types.

[0093] The first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b exemplarily further include a binder and / or a conductive agent; the amount and / or type of the binder of the two may be the same or different, and the amount and / or type of the conductive agent of the two may be the same or different.

[0094] Among the parameters related to the parameter H value, the thickness value corresponding to each structure refers to its dimension in the thickness direction A of the positive electrode sheet, which can be tested by conventional methods, such as by scanning electron microscope. Taking the positive electrode active material layer 2212 consisting of the first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b as an example, refer to Figure 1 The total thickness of the positive electrode active material layer 2212 is represented by htotal, the thickness of the first positive electrode active material layer 2212a is represented by h1, and the thickness of the second positive electrode active material layer 2212b is represented by h2. htotal=h1+h2, H=h1 / htotal.

[0095] The lattice volume shrinkage rate refers to the volume shrinkage percentage of the material lattice in the fully charged state relative to the fully discharged state, with v1 representing the material lattice volume in the fully discharged state, and v2 representing the material lattice volume in the fully charged state, V = (v1-v2) / v1. The material lattice volume can be tested by conventional methods, such as X-ray diffraction (XRD) testing.

[0096] In the embodiments of the present application, the value of V / H is, for example but not limited to, any point value among 3.3%, 6.6%, 7.7%, 8.5%, 10.0%, 14.3%, 20.0%, 24.0%, 28.6% or a range value between any two of them.

[0097] In the technical solution of the embodiment of the present application, the ratio between the lattice shrinkage rate of the outer positive electrode active material and the thickness ratio of the inner active material layer is regulated to meet a certain range, so that the adjacent active material layers have a more matched charge and discharge capacity, which is beneficial to improving the cycle stability.

[0098] In some embodiments, V and H satisfy the following relationship:

[0099] In these embodiments, the ratio of the V value to the H value satisfies a further range, so that adjacent active material layers have more matched charge and discharge capabilities, which is beneficial to better improve the cycle stability.

[0100] In some embodiments, the value of V satisfies: 2%≤V≤4%; optionally, the value of V satisfies: 2%≤V≤3%.

[0101] As an example, the value of V is, for example but not limited to, any one of 2%, 2.5%, 3%, 3.5%, 4%, or a range of any two thereof.

[0102] It should be noted that in other embodiments of the present application, the value of V may also be 1% to 4%, 1% to 5%, 1% to 6%, 2% to 5% or 2% to 6%.

[0103] In these embodiments, the second positive electrode active material has a smaller lattice shrinkage rate, which is beneficial to improve the cracking and breaking of the second positive electrode active material; at the same time, it is beneficial to control the ratio of the V value to the H value within a suitable range, which can improve the cycle stability. In addition, when the V value condition is met, there are more ternary positive electrode materials (such as nickel-cobalt-manganese ternary materials) to choose from, which is beneficial to improve the energy density.

[0104] In some embodiments, the value of H satisfies: 14%≤H≤61%; optionally, the value of H satisfies: 14%≤H≤39%.

[0105] As an example, the value of H is, for example but not limited to, any one of 14%, 19%, 29%, 39%, 49%, 61%, or a range of values ​​between any two of them.

[0106] It should be noted that in other embodiments of the present application, the value of H may also be 10% to 61%, 10% to 64%, 10% to 71%, 12% to 61%, 12% to 64% or 12% to 71%.

[0107] In these embodiments, the thickness ratio of the inner active material layer meets a certain range. When the ratio requirements of the V value and the H value are met, the V value can meet a suitable range, which is conducive to better improving the cycle stability. At the same time, it is conducive to better matching the first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b and exerting their respective functions; when the first positive electrode active material in the first positive electrode active material layer 2212a includes a highly stable lithium-containing phosphate, the thickness ratio of the first positive electrode active material layer 2212a is above a certain standard, and the first positive electrode active material layer 2212a also has a certain charge and discharge capacity, which is conducive to improving the cycle stability.

[0108] In some embodiments, the first positive electrode active material layer 2212a includes a first positive electrode active material, and the specific surface area BET of the first positive electrode active material satisfies: 7m 2 / g≤BET≤24m 2 / g; Optionally, BET satisfies: 9m 2 / g≤BET≤22m 2 / g.

[0109] The specific surface area can be tested by conventional methods, for example, by weighing a certain mass of the first positive electrode active material and then testing it by a specific surface area and porosity analyzer.

[0110] As an example, the specific surface area BET of the first positive electrode active material is, for example but not limited to, 7 m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g Any point value or any range of values ​​between them.

[0111] In these embodiments, the specific surface area BET of the first positive electrode active material is above a certain standard, so that it has good electrochemical activity; the specific surface area BET of the first positive electrode active material is below a certain standard, which can improve the deterioration of the cycle stability caused by water absorption of the material.

[0112] In some embodiments, the first positive electrode active material layer 2212a includes a first positive electrode active material, the first positive electrode active material includes a doped or undoped lithium-containing phosphate; and / or the second positive electrode active material includes a ternary positive electrode material.

[0113] The lithium-containing phosphate may contain or not contain doping elements, such as but not limited to materials consisting of lithium sodium iron phosphate, lithium manganese iron phosphate, lithium manganese iron phosphate and doping elements.

[0114] Ternary positive electrode materials include, for example, NCM (nickel cobalt manganese) based materials, NCA (nickel cobalt aluminum) based materials, and the like.

[0115] In these embodiments, the lithium-containing phosphate has good stability, and the ternary positive electrode material has a high energy density, which is beneficial to achieve both good cycle stability and energy density.

[0116] In some embodiments, the lithium-containing phosphate includes Li 1+x Mn 1-y Ay P 1-z E z O4, where -0.100 ≤ x ≤ 0.100, 0.001 ≤ y ≤ 0.500, 0.001 ≤ z ≤ 0.100, element A includes one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb or Ge, and element E includes one or more of B, Si, N, S, F, Cl or Br.

[0117] Optionally, element A includes one or more of Fe, Ti, V, Ni, Co or Mg.

[0118] Optionally, element E includes one of B, Si, N and S.

[0119] In these embodiments, the lithium-containing phosphate has good electrochemical properties, such as good stability.

[0120] In some embodiments, the ternary cathode material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, element M1 includes Mn and / or Al, element M2 includes one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W or Nb, and element R includes one or more of N, F, S or Cl.

[0121] In the embodiments of the present application, the chemical formulas of the lithium-containing phosphate and the ternary cathode material can be tested by conventional methods, such as measuring the element composition by ICP (Inductively Coupled Plasma Emission Spectrometer).

[0122] In these embodiments, the ternary cathode material has good electrochemical properties, such as high energy density, appropriate lattice shrinkage rate, etc.

[0123] In some embodiments, the lithium-containing phosphate includes Fe element, and the ternary cathode material includes Mn element; in the positive electrode active material layer 2212, the mass ratio of Fe element to Mn element is 0.03 - 0.25.

[0124] Optionally, the lithium-containing phosphate is a material composed of lithium iron manganese phosphate and doped elements; the ternary cathode material is a nickel cobalt manganese ternary material and does not contain Fe element.

[0125] As an example, the mass ratio of Fe element to Mn element is, for example but not limited to, any one of 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, and 0.25, or a range between any two of them.

[0126] It should be noted that in other embodiments of the present application, the mass ratio of Fe element to Mn element may also be 0.02-0.25, 0.02-0.26, 0.02-0.27, 0.02-0.28, 0.03-0.26, 0.03-0.27 or 0.03-0.28.

[0127] The mass ratio of Fe and Mn elements can be tested by conventional methods, for example, placing the positive electrode plate 221 in an acid solution or other treatment solution to digest the positive electrode active material layer 2212, and then measuring the mass fractions of Fe and Mn elements by ICP, and calculating the mass ratio of Fe and Mn elements based on this.

[0128] In these embodiments, the mass ratio of the Fe element to the Mn element satisfies a certain range, which is beneficial for regulating the H value within a suitable range, thereby better improving the cycle stability.

[0129] In some embodiments, in the positive electrode active material layer 2212 , the mass ratio of Fe element to Mn element is 0.05 to 0.20.

[0130] In these embodiments, the mass ratio of the Fe element to the Mn element satisfies a further range, which is beneficial for regulating the H value within a more appropriate range, thereby better improving the cycle stability.

[0131] In some embodiments, the positive electrode active material also includes at least one or less coating layer coated on at least a portion of the surface of the first positive electrode active material and / or the second positive electrode active material, the coating layer includes one or more of oxides, nitrates, phosphates or carbonates containing specified elements, and the specified elements include one or more of Al, Ba, Zn, Ti, Co, W, Y, Si, Sn, B or P; the coating layer includes one or more of pyrophosphate, phosphate or carbon.

[0132] As an example, the coating layer coated on at least part of the surface of the first positive electrode active material is the first coating layer, and the first coating layer is, for example, coated on at least part of the surface of the lithium-containing phosphate. The first coating layer includes one or more of oxides, nitrates, phosphates or carbonates containing the specified element.

[0133] As an example, the coating layer coated on at least part of the surface of the second positive electrode active material is the second coating layer, which is coated on at least part of the surface of the ternary positive electrode material, for example. The second coating layer includes one or more of pyrophosphate, phosphate or carbon.

[0134] Optionally, the second coating layer includes one or more of Al2O3, B2O3 or TiO2.

[0135] The first coating layer can fully or partially coat the lithium-containing phosphate, and can be one or more layers, and the materials between different layers can be the same or different. Similarly, the second coating layer can fully or partially coat the ternary positive electrode material, and can be one or more layers, and the materials between different layers can be the same or different.

[0136] In these embodiments, the coating layer can modify the positive electrode active material.

[0137] See also Figure 5 In some embodiments, the positive electrode plate 221 further includes a hydrophobic conductive layer 2213 , the hydrophobic conductive layer 2213 is located between the first positive active material layer 2212 a and the second positive active material layer 2212 b , and the hydrophobic conductive layer 2213 includes a hydrophobic conductive material.

[0138] The hydrophobic conductive material may be a material having both hydrophobicity and conductivity, or may be a combination of a hydrophobic material and a conductive material.

[0139] Optionally, the water contact angle of the hydrophobic conductive material is greater than 130°.

[0140] The hydrophobic conductive layer 2213 may contain not only the hydrophobic conductive material but also an adhesive and the like.

[0141] It should be noted that the hydrophobic conductive layer 2213 is only located between the first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b, but it does not belong to the positive electrode active material layer 2212. In other words, when calculating the H value, the thickness of the hydrophobic conductive layer 2213 is not included in the total thickness htotal of the positive electrode active material layer 2212.

[0142] In these embodiments, the hydrophobic conductive layer 2213 has both hydrophobic and conductive functions. The conductive function enables the first positive electrode active material layer 2212a and the second positive electrode active material layer 2212b to maintain good conductivity, and the hydrophobic function is beneficial to improving cycle stability.

[0143] In some embodiments, the hydrophobic conductive material includes a hydrophobic conductive polymer and a hydrophobic conductive carbon.

[0144] In these embodiments, the combination of the hydrophobic conductive polymer and the hydrophobic conductive carbon can provide better conductivity and hydrophobicity.

[0145] In some embodiments, the hydrophobic conductive polymer includes one or more of polypyrrole, polyaniline, polythiophene, or polyacetylene; and / or the hydrophobic conductive carbon includes one or more of hydrophobic carbon nanotubes or hydrophobic carbon nanofibers.

[0146] Optionally, the hydrophobic conductive polymer comprises polythiophene and / or polyaniline; as an example, the hydrophobic conductive polymer is polyaniline.

[0147] In these embodiments, the hydrophobic conductive polymer and the hydrophobic conductive carbon are appropriately selected and can better meet the performance requirements of the hydrophobic conductive material.

[0148] In some embodiments, in the hydrophobic conductive material, the mass proportion of the hydrophobic conductive carbon is 2% to 10%.

[0149] As an example, the mass proportion of the hydrophobic conductive carbon is, for example but not limited to, any point value among 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, or a range value between any two of them.

[0150] In these embodiments, the hydrophobic conductive carbon has a suitable mass proportion in the hydrophobic conductive material, so that the performance requirements for the hydrophobic conductive material can be better met.

[0151] In a second aspect, an embodiment of the present application provides a battery 100, comprising the positive electrode plate 221 of the above embodiment.

[0152] In a third aspect, an embodiment of the present application provides an electrical device, comprising the battery 100 of the above embodiment.

[0153] Some specific embodiments are listed below to better illustrate the present application.

[0154] 1. Preparation of battery cells

[0155]

Preparation of positive electrode

[0156] Preparation of the first positive electrode active material layer: The first positive electrode active material lithium manganese iron phosphate and the material composed of doping elements (chemical formula LiMn 0.6 Fe 0.4 P 0.995 S 0.005O4), conductive carbon, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5, and the mixture is stirred and mixed to obtain a first coating layer slurry, and the viscosity is controlled to be 3000mPa·S~10000mPa·S; the first coating layer slurry is coated on an aluminum foil, and a first positive electrode active material layer is formed on the positive electrode collector after drying.

[0157] Preparation of the second positive electrode active material layer: The positive electrode active material was replaced with the same mass of NCM (chemical formula: LiNi 0.55 Co 0.05 Mn 0.4 ) to obtain a second coating layer slurry; coating the second coating layer slurry on the first positive electrode active material layer, and forming a second positive electrode active material layer on the first positive electrode active material layer after drying.

[0158] The positive electrode sheet is obtained through rolling and die cutting.

[0159] in:

[0160] In the embodiment containing the hydrophobic conductive layer, before preparing the second positive electrode active material layer, a hydrophobic conductive layer is first formed on the first positive electrode active material layer, and then the second positive electrode active material layer is formed on the hydrophobic conductive layer.

[0161] Preparation of the hydrophobic conductive layer: A hydrophobic conductive material is composed of polyaniline and hydrophobic carbon nanotubes, in which the hydrophobic carbon nanotubes account for 4 wt %; the hydrophobic conductive material is formulated into a slurry, and then coated on the first positive electrode active material layer to form a hydrophobic conductive layer with a thickness of 8 μm.

[0162]

Preparation of negative electrode sheet

[0163] Graphite, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), and conductive carbon are added to a certain amount of deionized water, with the mass ratio of graphite: sodium carboxymethyl cellulose: styrene-butadiene rubber: conductive agent being 90:2:3:5, and stirred to form a uniform negative electrode slurry, with the viscosity controlled to be 3000Pa·S~10000mPa·S; the negative electrode slurry is coated on copper foil, and the negative electrode sheet is formed after drying, cold pressing, and slitting.

[0164]

Preparation of electrolyte

[0165] Contains LiPF6, the concentration of which in the electrolyte is 1 mol / L. The solvent includes ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. It also contains fluoroethylene carbonate (FEC), the content of which in the electrolyte is 5wt%.

[0166]

Preparation of isolation film

[0167] A polyethylene (PE) porous polymer film is used as the isolation membrane.

[0168]

Preparation of lithium-ion batteries

[0169] The prepared positive electrode sheet, negative electrode sheet and isolation film are made into corresponding battery cells according to the Z-shaped stacking structure; the battery cell is vacuum dried at 90°C for 12 hours, and then the positive electrode tabs and negative electrode tabs are ultrasonically welded. The positive electrode sheet adopts aluminum tabs, and the negative electrode sheet adopts nickel tabs. The positive electrode tabs and negative electrode tabs are located on the same side of the battery cell; the battery cell after welding the tabs is loaded into an aluminum-plastic film of a suitable size for top-side sealing packaging. The top-side sealing temperature is 145°C, and the electrolyte is injected, and the battery cell is allowed to stand, formed, aged, exhausted, sealed twice, and capacity tested to obtain the prepared soft-pack stacked battery cell.

[0170] 2. Test Method

[0171] 1. Test of lattice volume shrinkage (V value) of the second positive electrode active material

[0172] The battery cell prepared by the above experimental method is used as the test object.

[0173] The fresh positive electrode was tested, and the a-axis and c-axis (material unit cell parameters) values ​​required for calculating the unit cell volume of the NCM material were calculated through XRD data and RietVeld software refinement. Then, the NCM material lattice volume of the fresh positive electrode was calculated using the formula v1=a^2×c×sin120°, which can be used to represent the NCM material lattice volume in the full discharge state, recorded as v1; at a constant temperature of 25°C, 2.5V~4.4V, it was charged to 4.4V according to 0.5C0, and then Charge at a constant voltage of 4.4V until the current is ≤0.05C0, then disassemble the battery, remove the positive electrode sheet, and perform XRD testing; through XRD data and RietVeld software refinement, the a-axis and c-axis (material unit cell parameters) values ​​required for calculating the unit cell volume of the NCM material in the fully charged state can be obtained, and then the formula v2=a^2×c×sin120° is used to calculate the lattice volume of the NCM material in the fully charged state, recorded as v2; in the above calculation formula, a and c correspond to the a-axis and c-axis unit cell parameter values, respectively.

[0174] Calculate the lattice volume shrinkage, lattice volume shrinkage = (v1-v2) / v1.

[0175] 2. Test of the ratio of the thickness of the first positive electrode active material layer to the total thickness of the positive electrode active material layer (H value)

[0176] The positive electrode sheet was cut into 11 mm × 10 mm, and the cut positive electrode sheet was placed in a thermos cup filled with liquid nitrogen and soaked for 10 min. The sample was taken out with tweezers and quickly broken with a knife. A relatively flat cross section was taken as a sample and placed on the sample table. It was processed and tested using an IB-19500CP ion milling instrument and a ZEISS SEM (Sigma 300) electron scanning microscope, and the cross-sectional morphology was observed. The thickness h1 of the first positive electrode active material layer and the total thickness htotal of the positive electrode active material layer were marked with the equipment.

[0177] Calculate the H value, H = h1 / htotal.

[0178] 3. Specific surface area (BET) test of the first positive electrode active material

[0179] The first positive electrode active material particles (LiMn 0.6 Fe 0.4 P 0.995 S 0.005 O4) until the required sample amount reaches 8 g, which is then placed in a fully automatic specific surface area and porosity analyzer (TristarⅡ3020), and the material BET is tested according to the test equipment program.

[0180] 4. Test of the mass ratio of Fe and Mn in the active material layer (Fe / Mn mass ratio)

[0181] Take 0.4g of the positive electrode piece in a 25ml beaker, add 2ml~5ml nitric acid, leave it overnight, then place it on a hot plate, heat it at about 100℃ (use a voltage-regulating transformer to adjust the input voltage and temperature), add 0.5ml perchloric acid after the positive electrode piece is digested, and heat it at about 140℃ until the white smoke is gone. The residue should be white, otherwise nitric acid and perchloric acid should be added to repeat the digestion, and finally use 7% (volume percentage of acid) hydrochloric acid to dissolve and extract. After the volume is fixed to an appropriate volume depending on the content of the element to be measured, the mass fraction of Mn and Fe is tested on the ICP-OES inductively coupled plasma emission spectrometer to calculate the Mn / Fe mass ratio.

[0182] 5. Cycle stability test

[0183] The prepared soft-pack laminated battery was charged to 4.4V at 0.5C0 at 2.5V-4.4V at a constant temperature of 25°C, and then charged at a constant voltage at 4.4V to a current ≤ 0.05C0, allowed to stand for 5 minutes, and then discharged to 2.5V at 1C0. The capacity was recorded as Cn (n = 1, 2, 3...), and the above operation was repeated. The capacity retention rate was calculated according to the ratio of Cn / C3. When Cn / C3×100%=80%, the corresponding number of cycles was extracted as an examination indicator of the cycle capacity.

[0184] 3. Experimental conditions and test results

[0185] The main experimental conditions in each experimental group are shown in Table 1. For experimental conditions not recorded, please refer to the above records for details, and this article will not repeat them again; the test results of cyclic stability are also shown in Table 1.

[0186] Table 1. Main experimental conditions and cycle stability test results

[0187]

[0188]

[0189] A brief analysis based on Table 1 is as follows:

[0190] In Examples 1 to 12, all of them satisfy In Comparative Examples 1 to 2, none of them satisfies Compared with Comparative Examples 1 to 2, the number of cycles when the cycle retention rate of Examples 1 to 12 is 80% is improved to varying degrees, indicating that the cycle stability is improved to varying degrees.

[0191] In Examples 1 to 5, Examples 2 to 4 further satisfy Compared with other embodiments, the number of cycles when the cycle retention rate of embodiments 2 to 4 is 80% is better, indicating better cycle stability.

[0192] In Examples 1 to 7, Examples 1 to 5 also satisfy 2%≤V≤4%, 14%≤H≤61%, while Examples 6 and 7 do not satisfy 2%≤V≤4%, 14%≤H≤61%. Compared with Examples 6 and 7, the number of cycles when the cycle retention rate is 80% in Examples 1 to 5 is improved to varying degrees, indicating that the cycle stability is improved to varying degrees.

[0193] In Example 3, Example 8 to Example 11, the BET of the first positive electrode active material is different. Among them, Example 3, Example 8 and Example 9 satisfy 9m 2 / g≤BET≤22m 2 / g, compared with other embodiments, the number of cycles when the cycle retention rate is 80% in Embodiment 3, Embodiment 8 and Embodiment 9 is better, indicating better cycle stability.

[0194] Compared with Example 3 and Example 12, a hydrophobic conductive layer is further provided in Example 12. Compared with Example 3, the number of cycles when the cycle retention rate of Example 12 is 80% is better, indicating better cycle stability.

[0195] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the second positive electrode active material layer is located outside the first positive electrode active material layer, and the second positive electrode active material layer includes a second positive electrode active material; The thickness of the first positive electrode active material layer accounts for H in the total thickness of the positive electrode active material layer, in %. The lattice volume shrinkage rate of the second positive electrode active material is V, in %. The relationship between V and H satisfies:

2. The positive electrode sheet according to claim 1, characterized in that: The V and H satisfy the following relationship:

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The value of V satisfies: 2%≤V≤4%; Optionally, the value of V satisfies: 2%≤V≤3%.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The value of H satisfies: 14%≤H≤61%; Optionally, the value of H satisfies: 14%≤H≤39%.

5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The first positive electrode active material layer includes a first positive electrode active material, and the specific surface area BET of the first positive electrode active material satisfies: 7m 2 / g≤BET≤24m 2 / g; Optionally, the BET satisfies: 9m 2 / g≤BET≤22m 2 / g.

6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: The first positive electrode active material layer includes a first positive electrode active material, and the first positive electrode active material includes a doped or undoped lithium-containing phosphate; and / or The second positive electrode active material includes a ternary positive electrode material.

7. The positive electrode sheet according to claim 6, characterized in that: The lithium-containing phosphate includes Li 1+x Mn 1-y A y P 1- z E z O4, -0.100≤x≤0.100, 0.001≤y≤0.500, 0.001≤z≤0.100, element A includes one or more of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb or Ge, and element E includes one or more of B, Si, N, S, F, Cl or Br; and / or The ternary cathode material includes Li a Ni b Co c M1 d M2 e O f R g , 0.75 ≤ a ≤ 1.2, 0.4 < b < 0.7, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, the element M1 includes Mn and / or Al, the element M2 includes one or more of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W or Nb, and the element R includes one or more of N, F, S or Cl.

8. The positive electrode sheet according to claim 6 or 7, characterized in that: The lithium-containing phosphate includes Fe element, and the ternary positive electrode material includes Mn element; in the positive electrode active material layer, the mass ratio of Fe element to Mn element is 0.03 to 0.25; Optionally, in the positive electrode active material layer, the mass ratio of Fe element to Mn element is 0.05 to 0.

20.

9. The positive electrode sheet according to any one of claims 6 to 8, characterized in that: The positive electrode active material further includes at least one coating layer described below coated on at least a portion of the surface of the first positive electrode active material and / or the second positive electrode active material, wherein: The coating layer includes one or more of oxides, nitrates, phosphates or carbonates containing a specified element, wherein the specified element includes one or more of Al, Ba, Zn, Ti, Co, W, Y, Si, Sn, B or P; and / or The coating layer includes one or more of pyrophosphate, phosphate or carbon.

10. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: The positive electrode plate further includes a hydrophobic conductive layer, the hydrophobic conductive layer is located between the first positive electrode active material layer and the second positive electrode active material layer, and the hydrophobic conductive layer includes a hydrophobic conductive material.

11. The positive electrode sheet according to claim 10, characterized in that: The hydrophobic conductive material includes a hydrophobic conductive polymer and a hydrophobic conductive carbon.

12. The positive electrode sheet according to claim 11, characterized in that: The hydrophobic conductive polymer includes one or more of polypyrrole, polyaniline, polythiophene or polyacetylene; and / or The hydrophobic conductive carbon includes one or more of hydrophobic carbon nanotubes and hydrophobic carbon nanofibers.

13. The positive electrode sheet according to claim 11 or 12, characterized in that: In the hydrophobic conductive material, the mass proportion of the hydrophobic conductive carbon is 2% to 10%.

14. A battery, characterized in that: It comprises the positive electrode sheet as claimed in any one of claims 1 to 13.

15. An electrical equipment, characterized in that: Comprising the battery of claim 14.

Citation Information

Patent Citations

  • Secondary battery, battery module, battery pack and electric device

    CN115832175A

  • Positive pole piece, battery and electric equipment

    CN116247162A

  • Positive pole piece, secondary battery and electric equipment

    CN116314602A

  • Positive electrode active material, positive electrode plate, electrochemical apparatus comprising positive electrode plate, and electronic apparatus

    WO2023077373A1